2012
DOI: 10.1002/app.38883
|View full text |Cite
|
Sign up to set email alerts
|

Development of optically transparent ZnS/poly(vinylpyrrolidone) nanocomposite films with high refractive indices and high Abbe numbers

Abstract: A series of optically transparent ZnS-poly(vinylpyrrolidone) (PVP) nanocomposite films with high refractive indices and high Abbe numbers have been prepared. Mercaptoethanol (ME) capped ZnS nanoparticles (NPs) were introduced into the PVP polymer matrix via simple blending with high nanophase contents. ME-ZnS NPs of around 3 nm were prepared from zinc acetate and thiourea precursors in N,N-dimethylformamide using ME as a capping agent. Transparent nanocomposite films with high refractive indices and high Abbe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The main purpose behind using zinc sulfide (ZnS) particles is also luminescent properties 71,72 or high RI materials. [73][74][75] Zhang et al 73 increased the RI of poly(vinylpyrrolidone) linearly from 1.5061 to 1.7523 with an increasing particle content up to 80 wt% while reducing the Abbe number. The transparency of thin films (thickness: 25 mm) above 500 nm was maintained.…”
Section: Zinc Sulfidementioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose behind using zinc sulfide (ZnS) particles is also luminescent properties 71,72 or high RI materials. [73][74][75] Zhang et al 73 increased the RI of poly(vinylpyrrolidone) linearly from 1.5061 to 1.7523 with an increasing particle content up to 80 wt% while reducing the Abbe number. The transparency of thin films (thickness: 25 mm) above 500 nm was maintained.…”
Section: Zinc Sulfidementioning
confidence: 99%
“…Young modulus [55] Tensile strength [55] Impact strength [56] Tensile strength [54] Young modulus [54] UV absorption [54] Thermal stability [42] Glass temperature [55] AlO 2 and Al 2 O 3 Antistatic properties [46] ATO Luminescence [66] CdS Luminescence [68] CdSe Elastic modulus [63] Elastic modulus [89] Tensile strength [64] Yield stress [89] Fracture Strain [89] Hardness [63] Glass Temperature [64] SiO 2 Magnetic properties [50,51] Fe 3 O 4 RI [43] CeO 2 RI [74] RI [75] RI [73] ZnS RI [77] RI [76] RI [78] PbS…”
Section: Influence Of the Particles On The Transparencymentioning
confidence: 99%
“…It has applications in photonic crystal sensors [1], heterojunction diodes [2], thin film photovoltaic cells [3][4][5][6][7], optical filters [8], light emitting diodes [9] and anti-reflection coatings [10]. Several methods have been employed to synthesize thin films including spray pyrolysis [11,12], solvothermal synthesis [13,14], sol-gel [2], successive ionic layer adsorption and reaction (SILAR) [15], pulsed laser deposition [16], close-space sublimation [17], metal-organic chemical vapor deposition (MOCVD), photo-assisted MOCVD [18], RF-mganetron sputtering [19,20], electrodeposition [21,22], thermal evaporation [23], aerosol assisted chemical vapor deposition (AACVD) [24,25], chemical bath deposition (CBD) [26][27][28][29][30][31][32][33][34] and film casting method [35,36]. Among these, CBD is potentially a simple, low temperature and cost effective method to high quality thin films.…”
Section: Introductionmentioning
confidence: 99%
“…According to eq , it is represented that there is the trade‐off relationship between a refractive index and an Abbe number: An Abbe number decreases corresponded to the increase of a refractive index of the material. Indeed, by adding ZnS as a filler to poly(vinylpyrrolidone) films, the refractive index increased with drastically decreasing Abbe numbers . From the series of reports on the development of high‐refractive index polymers, it was suggested that the dependency of the refractive index of alkyl sulfide skeletons on the light wavelength intrinsically is small, leading to a high Abbe number.…”
Section: Resultsmentioning
confidence: 99%